Investigation of the Collapsed Dolphin Structure of the Mahakam Bridge Using Bathymetry and Side-Scan Sonar After Collision - Efendi, Aco Wahyudi (Program Studi Teknik Sipil, 2025)
This study investigates the collapse of the dolphin (fender) structure of the Mahakam Bridge in Samarinda, Indonesia, following a collision with a timber-laden pontoon ship. High-resolution bathymetry and side-scan sonar (SSS) techniques were employed to map debris distribution, quantify structural damage, and assess risks to bridge integrity and navigational safety. The dolphin structure, critical for pier protection, suffered catastrophic failure, with debris fields extending 42.6–51.5 m laterally and covering 617.7–721 m². Bathymetric surveys revealed elevation anomalies of 1–1.5 m at depths of 4.5 m, while SSS identified cylindrical debris (diameter: 8 m) consistent with dolphin components. Integration of these methods enabled precise debris localization (00°50′13.29″ S, 117°18′24.51″ E) and informed relocation recommendations for navigation aids. The findings underscore the efficacy of remote sensing in turbid riverine environments and provide a framework for post-collision infrastructure assessment.